Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(x^3+8y^3+2xy^2+x^2y\)
\(=x^3+2x^2y-x^2y-2xy^2+4xy^2+8y^3\)
\(=x^2\left(x+2y\right)-xy\left(x+2y\right)+4y^2\left(x+2y\right)\)
\(=\left(x+2y\right)\left(x^2-xy+4y^2\right)\)
A= \(^{x^3+3x^2y-4xy^2-12y^3=x^2\left(x+3y\right)-4y^2\left(x+3y\right)=\left(x+3y\right)\left(x^2-4y^2\right)}\)
Trả lời:
Ta có: ( x - 2y )3 = x3 - 3.x2.2y + 3.x.( 2y )2 - ( 2y )3 = x3 - 6x2y + 12xy2 - 8y3 ( HĐT thứ 5 - lập phương của 1 hiệu )
=> Chọn b
Trả lời:
a, \(\left(x^2-2y\right)\left(x^4+2x^2y+4y^2\right)-x^3\left(x-y\right)\left(x^2+xy+y^2\right)+8y^3\)
\(=\left(x^2\right)^3-\left(2y\right)^3-x^3\left(x^3-y^3\right)+8y^3\)
\(=x^6-8y^3-x^6+x^3y^3+8y^3\)
\(=x^3y^3\)
b, \(\left(x-2\right)\left(x^2+2x+4\right)-\left(x-1\right)^3+7\)
\(=x^3-8-\left(x^3-3x^2+3x-1\right)+7\)
\(=x^3-8-x^3+3x^2-3x+1+7\)
\(=3x^2-3x\)
c, \(x\left(x+2\right)\left(2-x\right)+\left(x+3\right)\left(x^2-3x+9\right)\)
\(=x\left(4-x^2\right)+x^3+27\)
\(=4x-x^3+x^3+27\)
\(=4x+27\)
\(C=3.\left(x^2-8y^3-15\right)-3\left(x-2y\right)\left(x^2+2xy+4y^2\right)\)
\(=3x^2-24y^3-45-3\left[x\left(x^2+2xy+4y^2\right)-2y\left(x^2+2xy+4y^2\right)\right]\)
\(=3x^2-24y^3-45-3\left[\left(x^3+2x^2y+4xy^2\right)-\left(2x^2y+4xy^2+8y^3\right)\right]\)
\(=3x^2-24y^3-45-3\left(x^3+2x^2y+4xy^2-2x^2y-4xy^2-8y^3\right)\)
\(=3x^2-24y^3-45-3\left(x^3-8y^3\right)\)
\(=3x^2-24y^3-45-3x^3+24y^3\)
\(=3x^2-3x^3-45\)